2008
DOI: 10.4049/jimmunol.181.10.6747
|View full text |Cite
|
Sign up to set email alerts
|

Aging Impairs IFN Regulatory Factor 7 Up-Regulation in Plasmacytoid Dendritic Cells during TLR9 Activation

Abstract: Plasmacytoid dendritic cells (pDCs) are innate sensors that produce IFN-α in response to viral infections. Determining how aging alters the cellular and molecular function of these cells may provide an explanation of increased susceptibility of older people to viral infections. Hence, we examined whether aging critically impairs pDC function during infection with HSV-2, a viral pathogen that activates TLR9. We found that impaired IFN-α production by aged murine pDCs led to impaired viral clearance with aging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
113
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 56 publications
13
113
0
1
Order By: Relevance
“…Decline in IFN secretion by pDCs in aged subjects has been demonstrated to be due to defect in signaling mechanisms that result in impaired phosphorylation of Interferon Regulatory Factor-7 (IRF-7) (Sridharan et al 2010;Stout-Delgado et al 2008). More recently, Qian et al (2011) have reported decreased IFN-I secretion in monocyte derived DCs from older donors in response to West Nile virus due to decreased induction of STAT-1, IRF-7 and IRF-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decline in IFN secretion by pDCs in aged subjects has been demonstrated to be due to defect in signaling mechanisms that result in impaired phosphorylation of Interferon Regulatory Factor-7 (IRF-7) (Sridharan et al 2010;Stout-Delgado et al 2008). More recently, Qian et al (2011) have reported decreased IFN-I secretion in monocyte derived DCs from older donors in response to West Nile virus due to decreased induction of STAT-1, IRF-7 and IRF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported a decrease secretion of IFN-α by aged pDCs, which are the most potent IFN producing cells (Sridharan et al 2010;Stout-Delgado et al 2008;Diebold et al 2003;Jing et al 2009). Besides pDCs, the mDCs subset of DCs is also capable of producing robust amount of IFNs in response to viral infection (Katashiba et al 2011;Diebold et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several virus derived molecules such ssRNA or CpG were unable to elicit TLR7 or TLR9 activation [63,64]. It seems that the increased basal oxidative stress related to aging could be the underlying cause of the decreased upregulation of the interferon regulatory factors by TLRs [16,65] . There is still controversy around whether the TLRs response to stimulation is altered with aging in macrophages or mDCs.…”
Section: Dendritic Cell Functional Changes With Agingmentioning
confidence: 99%
“…• Chemotaxis decreased or no change [15,16,17] Free radical production decrease [15,16,17] Intracellular killing decreased [15,16,17] Rescue from apoptosis decreased [18] Intracellular signalling altered [14,19,20 Free radical production decrease [56] Intracellular killing decrease [56] Pro-inflammatory cytokine production increased [47,48,54,57] Intracellular signalling altered [29,47,48,49] Dendritic cells Phenotype no change or decrease [47,63,64] Subpopulations no change [63,64] Receptors number decrease or no change [29,65] Functions Phagocytosis decrease or no change [63,72,73] Antigen presentation decreased [63,72] Chemotaxis decreased [73] Intracellular killing decrease [63] Pro-inflammatory cytokine production increased [63,66,68] T cell priming altered [63,72] Cytokine production decreased or no change [84,88] T cell priming altered …”
Section: Innate Immunosenescence and Age-associated Pathologiesmentioning
confidence: 99%